China’s Policy on Development and Security in East Africa - Odgaard, Liselotte (Scientia Militaria - South African Journal of Military Studies, 2019)
This article argues that China’s Eastern Africa policy is based on Chinese national economic and strategic interests – but with significant contributions to regional order. Beijing couples its One Belt One Road (OBOR) initiative and existing United Nations (UN) policies to ensure that economic development projects are linked to Chinese contributions to regional peace and stability. China contributes to regional order by emphasising the use of military force for defensive purposes only and by gaining pre-approval from the region for such interventions. It also provides strong government-backed economic and diplomatic assistance to African countries, to further foster such regional order. Yet, contrary to its stated intentions, Beijing’s focus on development and non-interference could pose challenges to human rights observance and issues of social justice – by potentially allowing rogue regimes to jeopardise the basic security of individuals. In turn, this could further challenge regional order by spreading instability and conflict across borders.